Metacognition in joint discussion: an analysis of the patterns of interaction and the metacognitive content of the networked discussions in mathematics - Hurme, Tarja-Riitta; Palonen, Tuire; Järvelä, Sanna (Metacognition and learning, 2006)
The aim of this study was to examine metacognition in computer-supported collaborative problem solving. The subjects of the study were 13-year-old Finnish secondary school students (N=16). The Knowledge Forum learning environment was used to support student pairs' problem-solving task involving polygons in a geometry course. The data consist of the student pairs' posted computer notes (n=95). To examine metacognition in a social context in the networked discussions, the features and patterns of networked interaction, the metacognitive content of the computer notes and their relations were examined. To examine the features of networked interaction, the social network analysis measures were used. The patterns of networked interaction were displayed with the multidimensional scaling technique. In the analysis, metacognitive contents of the computer notes were categorized as metacognitive knowledge, metacognitive skills, and not metacognitive. Further, with the correspondence analysis, we examined how the student pairs' metacognitive activity was distributed. The results of the study revealed that the metacognitive activity varied among participants, although some aspects of metacognition such as planning never encountered. It was found that there is a relation between metacognitive activity and the features of interaction. The student pairs who monitored and evaluated the ongoing discussions had a strategically optimal position in the communication network. (www.springerlink.com/content/443m0m7470918t0u/?p=49230a173dd742e8bc0ec4f7f45b3327&pi=4)